Mortars containing sustainable PCM’s for the energy efficiency of buildings - Frigione, Mariaenrica (2019)
Energy use in buildings represents more than one-third of global energy consumption and contributes to nearly one-quarter of greenhouse gases emission worldwide. The thermal comfort demand represents one of the main cause of the increased energy consumption. To guarantee a thermal indoor comfort, contributing at the same time to the energy saving, the Thermal Energy Storage (TES) methodologies have recently gained interest. These technologies involve the use of a smart material, i.e. a Phase Change Material (PCM), with the capability to absorb/release energy from/in the environment; it can be easily integrated into a building material, such as a mortar. In this work, aerial lime-based mortar with the incorporation of an eco-sustainable PCM have been analyzed with the purpose to improve the energy efficiency of buildings. For its non-toxic nature, a thermoplastic polymer has been selected as PCM, i.e. Poly-Ethylene Glycol (PEG 1000). This material was included in an inert support obtained as byproduct of stone extraction from quarry. The final product, i.e. PEG/stone, can be regarded as a composite to be used as mortar aggregate. A preliminary (chemical and physical) characterization of this compound shown that the sustainable aggregates PEG/stone have an appropriate Latent Heat Thermal Energy Storage (LHTES). The addition of these aggregates into a mortar compositions lead to an unsuitable reduction of mechanical properties.